Peningkataan Minat Belajar Hidup Sederhana pada Siswa Sekolah Dasar melalui Metode Jigsaw - Enah Rahli; Aziza Aryati (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
This study aims to determine how much interest in learning simple life increased in elementary school students through the jigsaw method. The research method uses Classroom Action Research. This research was conducted at SDN 120 Seluma in 2023. The research subjects amounted to 14 students. Data collection using tests and observations. The stages of research include (1) planning; (2) implementation; (3) observation; (4) reflection. The results of the study obtained the results of learning interest in simple life in students increased after being given action with the teaching material of the jigsaw method. The results of students' interest in learning were obtained from observation sheets and questionnaires of interest in learning. The observation sheet is used when the teacher conducts learning, while the questionnaire is given to students at the end of learning activities. Based on observations of student interest in learning in cycles I and II.